Examining the Relationship Between English Reading Habits and Reading Comprehension Among Vocational School Students - Dinullah, Aqshol Cahya; Zamzam, Ahmad; Junaidi, Ahmad (Edukasiana: Jurnal Inovasi Pendidikan, 2026)
Reading habits are widely believed to influence academic achievement, yet empirical evidence from rural vocational school contexts remains limited, particularly in English as a Foreign Language (EFL) settings. This study examined the correlation between English reading habits and reading achievement among eleventh-grade students at SMKN 2 Sekotong, a rural vocational school in Indonesia. Employing a quantitative correlational design with ex post facto approach, data were collected from 30 students selected through simple random sampling. Reading habits were measured using a Reading Habits Questionnaire (4-point Likert scale), while reading achievement was assessed through a 30-item reading comprehension test covering narrative and descriptive texts. After normality testing revealed non-normal distribution of reading achievement scores, Spearman's rank-order correlation was employed for analysis. The analysis revealed no statistically significant correlation between reading habits and reading achievement (ρ = -0.023, p = 0.902), indicating a very weak relationship. Students with similar self-reported reading habits demonstrated vastly different comprehension outcomes, with some low-habit readers outperforming high-habit readers. These findings challenge universal assumptions about the reading habits-achievement relationship and suggest that factors such as cognitive load, text appropriateness, instructional quality, and contextual resources may play more substantial roles than reading frequency alone. The results emphasize the need for contextualized, quality-focused literacy interventions rather than quantity-based approaches in rural vocational education settings